Assessing the failure in transfer of passive immunity in beef calves: two case reports - Carolina Balao Silva (Instituto Politécnico de Viseu, 2020)
Introduction: Failure in Transfer of Passive Immunity (FTPI) is a condition that occurs frequently in the bovine species when inadequate ingestion or absorption of enough good-quality colostrum takes place. In bovine kept in extensive conditions, FTPI diagnosis is usually made by complete physical examination, with not enough time for laboratory analysis, and treatment is based on the administration of colostrum replacement products or transfusion.